Inferring sediment deposition trend in data scared wetland impacted by degraded urban catchment - Bhaswatee Baishya; Arup Kumar Sarma (International Journal of Sediment Research)
The reduction in water retention capacity due to sedimentation in wetlands poses a serious threat to the ecology of this imperative freshwater resource. This also increases the risk of flooding in the river catchment areas that feed these wetlands. Sediments are mostly produced by unplanned development and hillcutting in upstream catchments. Henceforth, it is crucial to understand the trend in sediment deposition to determine management measures. However, measuring sediment deposition in wetlands is challenging. This study investigates a novel and cost-effective approach to discover trends in sediment deposition within wetlands via geospatial techniques and compares their water extents in the Deepor Beel Wetland, a Ramsar site in Assam, India. The water spread areas were assessed via supervised classified Landsat images and the band rationing technique, i.e., the normalized difference pond index (NDPI). This study establishes that sedimentation causes the water level in wetlands to rise, resulting in an increase in the area of water spread. This often suggests that the lean period water volume is increasing, indicating better health of the stream-wetland ecosystem. However, this apparent increase in water volume is actually due to the displacement of water by the sediment that has been deposited on the bed over time. This approach has identified a reduction in the water holding capacity of the wetland to 9.19 million m3 in 18 years by utilizing geospatially derived water spread and elevation data from two years (2003 and 2021) with comparable rainfall. In the absence of recent and past years with comparable precipitation, the proposed method can still be applied by adjusting the apparent increase in volume by considering the difference in the net inflow volume between the two years of interest. The results of sediment transport toward the wetland, as computed by the Soil and Water Assessment Tool (SWAT) model while accounting for the sediment retention rate of the wetland, strongly agree with the proposed approach. The present approach can be extended to similar stream-wetland ecosystems to examine sediment dynamics and help create better management strategies for wetlands and associated catchment conservation and restoration.